Analysis ot The Influence of Exchange Rates, Inflation, and Investment on Indonesia's Export Value (1990 – 2024) - Lastri Lastri; Elvis F. Purba; Nancy Nopeline; Satrio Theophilus Telaumbanua (STABN RADEN WIJAYA WONOGIRI, 2021)
One way to boost Indonesia's economic growth is by increasing exports, resulting in a trade surplus. Inflation, investment, and exchange rates influence export value. This study uses the ARDL model to examine the influence of inflation, investment, and exchange rates on export value in both the short and long term. From the results of research using macroeconomic data, it can be seen that the inflation and investment variables have a significant positive effect on the value of Indonesian exports and the exchange rate variable has a significant negative effect in both the short and long term